2017
DOI: 10.1016/j.geomorph.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Underground riparian wood: Buried stem and coarse root structures of Black Poplar (Populus nigra L.)

Abstract: Despite the potential importance of tree species in influencing the processes of wood recruitment, transport, retention, and decay that control river wood budgets, focus has been relatively limited on this theme within fluvial wood research. Furthermore, one of the least investigated topics is the belowground living wood component of riparian trees. This paper presents observations of the morphology and age of buried stem and coarse root structures of eight Populus nigra individuals located in the riparian woo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 46 publications
0
27
0
3
Order By: Relevance
“…The present paper attempts to provide such information, specifically focussing on one widely‐occurring riparian tree species: Populus nigra L . Complementary research on the architecture of the coarsest root components of individuals of this species is reported elsewhere (Holloway et al , , ), whereas the present paper employs the trenching method to explore root profiles more generally to answer the following research questions: Is there an association between riparian tree root properties and depth within the bank profile? Does the association between root properties and depth within the bank profile vary with moisture availability? Is there an association between root properties and properties of the surrounding sediment? …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The present paper attempts to provide such information, specifically focussing on one widely‐occurring riparian tree species: Populus nigra L . Complementary research on the architecture of the coarsest root components of individuals of this species is reported elsewhere (Holloway et al , , ), whereas the present paper employs the trenching method to explore root profiles more generally to answer the following research questions: Is there an association between riparian tree root properties and depth within the bank profile? Does the association between root properties and depth within the bank profile vary with moisture availability? Is there an association between root properties and properties of the surrounding sediment? …”
Section: Introductionmentioning
confidence: 81%
“…Therefore, establishing such distributions has been the main motivation for field investigations of riparian root system structure, including the distributions of root area ratio (RAR) (sectional area of roots per unit sectional area of bank), root diameters (since breaking stress is dependent on size) and root density (frequency per unit area of bank section) through riparian sediments. With the exception of one study in which coarse roots of over 1 cm diameter were observed in eroding banks from a boat (Rood et al , ), another in which whole tree root systems were removed from man‐made canal, dam and flood protection dikes (Vennetier et al , ; Zanetti et al , ), and two recent papers in which the coarse root architecture of eight individual mature Populus nigra trees was investigated and interpreted (Holloway et al ., , ), riparian root investigations have been conducted using the wall‐profile or ‘trenching’ method (Maeght et al , ), where exposed roots are investigated in excavated vertical sediment profiles. Some early excavations by Abernethy and Rutherfurd () and Simon and Collison () found a steep (near exponential) decline in root numbers with depth, although this only approached a steady curve at distances of several metres from the trunks of nearby trees, at which point numbers and area of roots became extremely low, and depth distributions of RAR varied dramatically with species and site.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of floodplain deposition (Hupp and Bazemore, 1993;Scott et al, 1997;Friedman et al, 2005;Holloway et al, 2017) and erosion (Simon and Hupp, 1987;GĂ€rtner et al, 2001;GĂ€rtner, 2007) have been estimated using dendrochronology. Specific dendrochronologic techniques have been developed to pinpoint the depth of germination of buried floodplain trees and to determine the age of germination (Hupp and Bazemore, 1993;Scott et al, 1997;Holloway et al, 2017). Specific dendrochronologic techniques have been developed to pinpoint the depth of germination of buried floodplain trees and to determine the age of germination (Hupp and Bazemore, 1993;Scott et al, 1997;Holloway et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Sigafoos (1964) noted that the new growth of the buried stem of a tree (we use the term 'stem' rather than the term 'trunk') anatomically resembled a root rather than a stem, displaying root-like characteristics such as increased vessel size (Nanson and Beach, 1977;Friedman et al, 2005), a reduction in ring width (Rubtsov and Salmina, 1983;Friedman et al, 2005), and increasingly diffuse annual ring boundaries (Friedman et al, 2005). Anatomical signatures of burial were not as prominent in black poplar (Populus nigra) (Holloway et al, 2017), and were not observed in a controlled study of mature pedunculate oak (Quercus robur) trees (Copini et al, 2015). These observations have been recorded for relatively few tree species including tamarisk (Tamarix ramosissima), sandbar willow (Salix exigua) (Friedman et al, 2005;Dean et al, 2011) and other willow (Salix) species (Rubstov and Salmina, 1983), green ash (Fraxinus pennsylvanica) (Sigafoos, 1964), and balsam poplar (Populus balsamifera) (Nanson and Beach, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…capable of resprouting) on bar surfaces during the falling limb of flood events, through an initial pioneer island phase of sprouting and sediment retention, to an established island phase as a result of the aggradation, enlargement and coalescence of pioneer islands. Since 2001, a number of refinements to the conceptual model have been introduced (Gurnell and Petts, ; Gurnell et al, , ), and empirical evidence has been presented to support specific aspects of the model, including for example, island morphological (Bertoldi et al, ), sedimentological (Gurnell et al ., ), soil (Mardhiah et al, ; BĂ€tz et al, ), and vegetation development (Francis et al, ; Perona et al, ); living wood recruitment and dynamics (Bertoldi et al, ); early growth rates of tree seedlings, cuttings and deposited trees (Francis et al, ; Francis et al, ; Francis and Gurnell, ; Francis, ; Moggridge and Gurnell, ) and interactions among developing subsurface tree root and shoot biomass and sediment retention (Holloway et al, , , ). In this paper we integrate empirical evidence of the processes and forms that accompany island evolution over decadal to event timescales, focusing on a single island‐braided reach of the Tagliamento River, Italy.…”
Section: Introductionmentioning
confidence: 99%